2012
DOI: 10.1097/bsd.0b013e318211fc4e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Segmental Motor Paralysis After Cervical Laminoplasty Using Intraoperative Spinal Cord Monitoring With Transcranial Electric Motor-evoked Potentials

Abstract: There were no abnormal findings on transcranial electric motor-evoked potential monitoring even in those patients who developed postoperative C5 palsy. These results indicate that the development of postoperative segmental motor paralysis after cervical laminoplasty occurs even if there are no abnormal findings during intraoperative monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Nassr et al [8] defined C5 palsy as loss of motor strength in the deltoid and/or biceps brachii, sensory deficit in the C5 distribution, or increased pain in the C5 distribution as compared with the preoperative status. Nakamae et al [16] defined C5 palsy as postoperative motor palsy of the deltoid and biceps muscles in the upper extremity by ≥1 grades in the manual muscle test (MMT) without sensory disturbance. These results highlight the need of a standard definition of C5 palsy in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nassr et al [8] defined C5 palsy as loss of motor strength in the deltoid and/or biceps brachii, sensory deficit in the C5 distribution, or increased pain in the C5 distribution as compared with the preoperative status. Nakamae et al [16] defined C5 palsy as postoperative motor palsy of the deltoid and biceps muscles in the upper extremity by ≥1 grades in the manual muscle test (MMT) without sensory disturbance. These results highlight the need of a standard definition of C5 palsy in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, eight studies reported that patients diagnosed with OPLL had a higher tendency to develop C5 palsy than those with multilevel CDH or CSM. 3,6,16,21,24,[28][29][30] Therefore, the type of disease had a significant relationship with postoperative C5 palsy development.…”
Section: 5242627mentioning
confidence: 99%
“…Nassr et al determined that the incidence of C5 nerve palsy after cervical spine decompressive procedures was 6.7%, with an increased risk in male patients 22 ; Nakamae et al found that the incidence was 3.8% in males, which was significantly higher than the incidence in females of 1.9%. 16 The remaining five studies found no correlation between gender distribution of patients and C5 palsy after surgery.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations